Description et usages d'un nouveau dispositif de vidéo-cours : l'encre numérique - Marc Trestini; Eric Christoffel; Isabelle Rossini (Université de Provence, 2010)
This paper presents a new design of video courses for university teaching. It is called "digital ink". It shows its impact on student learning and describes the cognitive profile of students for which this device seems to produce the best results. The device which is studied consists of a Tablet PC combined with a work agenda on line. The Tablet PC enables one to project what the teacher traditionally wrote on the board. That is to say; explanatory notes, equations and hand-written diagrams. The teacher has a writing tool (digital light pen) which allows cursive script (handwriting) on a computer. All written records produced by the teacher during the course, accompanied by verbal comments are recorded. The study of this device is based on student performance on exams, how often they consulted the videos as well as the manner of consulting them. This study shows the impact of this new device on student learning according to their cognitive profile.